Reducing risks to food security from climate change - Campbell, Bruce M.; Vermeulen, Sonja J.; Aggarwal, Pramod K.; Corner-Dolloff, Caitlin; Girvetz, Evan Hartunian; Loboguerrero Rodriguez, Ana María; Ramírez Villegas, Julián Armando; Rosenstock, Todd S.; Sebastian, Leocadio S.; Thornton, Philip K.; Wollenberg, Eva Karoline (Elsevier, 2016)
Climate change will have far-reaching impacts on crop, livestock and fisheries production, and will change the prevalence of crop pests. Many of these impacts are already measurable. Climate impact studies are dominated by those on crop yields despite the limitations of climate-crop modelling, with very little attention paid to more systems components of cropping, let alone other dimensions of food security. Given the serious threats to food security, attention should shift to an action-oriented research agenda, where we see four key challenges: (a) changing the culture of research; (b) deriving stakeholder-driven portfolios of options for farmers, communities and countries; (c) ensuring that adaptation actions are relevant to those most vulnerable to climate change; (d) combining adaptation and mitigation.